Changing the education paradigm in oncology: ESO masterclass, 17 years of continuous success. (February 2020) - Pavlidis, Nicholas; Peccatori, Fedro; Aapro, Matti; Rolfo, Christian; Cervantes, Andres; Stahel, Rolf; Eniu, Alex; Cavalli, Franco; Costa, Alberto
Abstract: In this review, we summarize the history of the 41 Masterclasses in Clinical Oncology (MCO) organized by ESO or ESO-ESMO during the last 17 years. MCOs have been held in five different geographical regions including: a) Central Europe, b) Eastern Europe and Balkans, c) Baltic and Euroasia, d) Arab World and Southern European Countries and e) Latin America. More than 2.000 young oncologists have attended and more than 250 distinguished faculty members have actively participated. The program exposes students to sessions covering all major tumors ("big killers") and to spotlights updating information on various important cancers and related topics. Participants are able to present their own clinical case in front of a tumor board or in parallel group sessions and are evaluated by a Learning Assessment Test (LAT) at the end of the event. They are asked to discuss the programme, using a questionnaire on the goals, quality and organization of the MCOs, which has been very highly scored by most of the participants. The Masterclass in Clinical Oncology has become the major educational event of ESO, intending to educate young oncologists from various countries within or outside Europe, providing an up-to-date interactive program based on solid evidence for all presented topics.